The Influence Of Online Marketing And Packaging On Purchasing Decisions For Sagarurung Sika Awan Fish In Pali District - Peryemi, Peryemi; Naruliza, Esty; Ermeila, Sri (Jurnal Fokus Manajemen, 2025)
This study aims to analyze the influence of digital marketing and product packaging on consumer purchasing decisions, both partially and simultaneously. The object of the study was the Sagarurung Sika Awan Fish UMKM located in Penukal Abab Lematang Ilir (PALI) Regency, with 201 respondents. The data obtained were analyzed through a series of statistical tests. The results of the validity test showed that all statement items in the questionnaire were declared valid, because the r-count value was greater than the r-table which was 0.164. The reliability test showed that the research instrument had good internal consistency, with a Cronbach's Alpha value exceeding 0.6. The normality test showed that the data was normally distributed. In addition, the results of the heteroscedasticity test carried out using a scatterplot did not identify a clear pattern, so it can be concluded that there were no symptoms of heteroscedasticity. The multicollinearity test also showed adequate results, with a Variance Inflation Factor (VIF) value of 2.343, which was below the threshold of 10, so there was no indication of multicollinearity. The results of the simultaneous regression analysis (F test) show that digital marketing and packaging variables have a significant influence on purchasing decisions, as reflected in the F-count value of 452.076 which is greater than the F-table of 2.33. Partially, the results of the t-test indicate that digital marketing has a significant influence on purchasing decisions, with a t-count value of 7.301, exceeding the t-table of 1.286, and a significance value of 0.000 which is smaller than 0.05. Likewise, packaging is also proven to have a significant influence with a t-count value of 13.530 and a significance value of 0.000 which is smaller than 0.05. Based on the contribution analysis, digital marketing contributes 33.6% to purchasing decisions, while packaging contributes 48.4%. The coefficient of determination (R²) value obtained of 0.820 indicates that 82% of the variation in purchasing decisions can be explained by the two independent variables. Meanwhile, the remaining 18% is influenced by other variables not covered in this study, such as competition factors, pricing policies, and economic conditions.